DRIS Norms for Pera Orange - Hernandes, Amanda [UNESP]; Souza, Henrique Antunes de; Amorim, Daniel Angelucci de [UNESP]; Natale, William [UNESP]; Lavres, Jose; Boaretto, Antonio Enedi; Camacho, Marcos Antonio (Taylor & Francis Inc, 2014)
Chemical analysis of leaves is an effective tool for detecting nutritional imbalances and providing data for fertilizer recommendations. Therefore, it is extremely important to establish criteria for interpreting these results. The DRIS (Diagnosis and Recommendation Integrated System) method is an alternative to the interpretation of results of leaf analysis as it allows the calculation of indexes for each nutrient, using its relations with others and comparing them with a reference population. Thus, we aimed to establish preliminary DRIS norms, by both Beaufils's and Jones's methods, and to derive critical levels and nutrient sufficiency ranges in the leaf tissue for Pera orange, by studying a commercial crop in the growing conditions of the Sao Paulo state. The methods (Beaufils and Jones) differed in the limiting nutrients in the Pera orange orchard. The use of regional norms must be prioritized because of differences between the management methods applied. In the methods used, the nutrients that had a greater number of concordant cases in decreasing order: Mn > Mg > B > N > Cu > Fe > Zn > K > P > Ca. Amplitudes related to the DRIS methods used were narrower than the conventional literature.
Keywords: nutritional diagnosis; nutritional assessment; Citrus sinensis L. Osbeck